Evaluation of Individual and Mixture Toxicity of Heavy Metals using Semi-continuous Type Sulfur Oxidizing Bacteria (SOB) Bioreactor - Seunggyu Kim; Heonseop Eom; Woochang Kang; Sang-Eun Oh (대한환경공학회지, 2022)
Objectives In this research, individual toxicity evaluation of heavy metals (Hg2+, Cr6+, Cd2+) was performed using a semi-continuous type bioreactor based on changes in the activity of sulfur oxidizing bacteria(SOB), and the purpose is to evaluate the toxic interaction of heavy metals through mixture toxicity evaluation and prediction modeling based on individual toxicity evaluation. Methods SOB were separated into a reactor, and then the culture medium and heavy metal influent were automatically injected at 1-hour intervals under the optimized conditions. Heavy metal mixture influent for composite toxicity evaluation was produced and tested based on the individual EC50 value of each heavy metal based on the change in electrical conductivity(EC). Based on the results of the mixture toxicity evaluation, the CA, IA, and CI models are implemented, and after comparison with the actual experimental values, similarity with the model was verified through the MDR index. And the type of interaction (synergism, antagonism) was evaluated by CI value. Results and Discussion In case of individual toxicity evaluation experiments, the individual EC50 of each heavy metal was derived at Hg2+ 0.71mg/L, Cr6+ 1.02 mg/L, and Cd2+ 8.82 mg/L in the order of strong toxicity. As a result of performing a combined toxicity evaluation based on individual EC50 values, it was judged that the combination of Hg2++Cd2+ showed a strong similarity with the IA model and no toxic interaction was developed, but all the remaining combinations were with the CI model. A similar relationship was shown and the existence of toxic interactions could be determined. As a result of analyzing the CI value, synergistic effects appeared in all combinations in which the interaction existed, and based on this result, it was possible to determine that Cr6+ is a factor that induces the toxic interaction. Conclusion This study allowed a real-time toxicity monitoring system for SOB to verify sensitive toxicity detection for functional and non-essential metals. In addition, most heavy metal combinations generate synergistic effects during toxic interactions, and additional research on heavy metals and organic pollutants other than heavy metals used in this study will result in a more systematic ecotoxicity monitoring system.